Mapping Information Technology Governance Using the Design Factor Framework COBIT 2019 at PT. XYZ - Afifah, Ummul; Adam, Steffi; Marfuah, Marfuah (Sistemasi: Jurnal Sistem Informasi, 2024)
PT. XYZ is a company based in the Riau Islands, specializing in the production of electric vehicle chargers and inverters. PT. XYZ has implemented information technology to meet its business needs. The purpose of this research is to achieve alignment between the business goals and the use of technology at PT. XYZ. The company has not yet utilized information technology governance to effectively support its objectives. Information technology governance mapping is carried out using the COBIT 2019 Framework mapping include processes EDM01, EDM03, EDM05, APO01, APO03, APO05, APO08, APO09, APO10, APO11, APO12, APO13, APO14, BAI02, BAI03, BAI05, BAI06, BAI07, BAI09, BAI10, DSS01, DSS02, DSS03, DSS04, DSS05, DSS06, MEA01, MEA02, MEA03, MEA04.